2019
DOI: 10.3892/ol.2019.10881
|View full text |Cite
|
Sign up to set email alerts
|

A predicted risk score based on the expression of 16 autophagy‑related genes for multiple myeloma survival

Abstract: Autophagy has an important role in the pathogenesis of plasma cell development and multiple myeloma (MM); however, the prognostic role of autophagy-related genes (ARGs) in MM remains undefined. In the present study, the expression profiles of 234 ARGs were obtained from a Gene Expression Omnibus dataset (accession GSE24080), which contains 559 samples of patients with MM analyzed with 54,675 probes. Univariate Cox regression analysis identified 55 ARGs that were significantly associated with event-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 82 publications
3
32
0
Order By: Relevance
“…Autophagy is an important mechanism in the processes of transporting damaged, denatured or aging proteins, digestion, and degradation of organelles. 15 These processes are mediated by autophagy-related genes (ARGs). Previous studies have identified more than 200 ARGs, directly or indirectly participating in the process of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an important mechanism in the processes of transporting damaged, denatured or aging proteins, digestion, and degradation of organelles. 15 These processes are mediated by autophagy-related genes (ARGs). Previous studies have identified more than 200 ARGs, directly or indirectly participating in the process of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Two published risk models were selected, one of which was a 16-gene signature [ 23 ] and the other was a 6-gene signature [ 24 ], compared with our 7-lncRNA signature. In order to make the model comparable, we use multifactor Cox analysis to calculate the risk score of the training set samples based on the corresponding genes in the model, evaluate the ROC of the two models, and divide the samples into high according to the optimal threshold.…”
Section: Resultsmentioning
confidence: 99%
“…We select 2 published related risk models, one of which is a 16-gene signature [ 23 ] and the other is a 6-gene signature [ 24 ], which was compared with our 7-lncRNA signature. The ROC and Kaplan-Meier (KM) survival curves of the published models in the training set and the C-index of the three models are plotted to compare the optimal models.…”
Section: Methodsmentioning
confidence: 99%
“…A nine-gene prognostic signature ( HLA-DPB1 , TOP2A , FABP5 , CYP1B1 , IGHM , FANCI , LYZ , HMGN5 , and BEND6 ) related to the ISS stage of MM was developed via weighted gene co-expression network analysis (WGCNA) and Lasso ( Liu et al, 2018 ). A 16-gene ( ATIC , BNIP3L , CALCOCO2 , DNAJB1 , DNAJB9 , EIF4EBP1 , EVA1A , FKBP1B , FOXO1 , FOXO3 , GABARAP , HIF1A , NCKAP1 , PRKAR1A , TM9SF1 , and SUPT20H ) prognostic model related to autophagy was also established by Lasso ( Zhu et al, 2019 ). Moreover, a six-gene risk score model ( ZNF486 , EPHA5 , RP11.326C3.15 , DUSP6 , DUSP10 , and TRIAP1 ) for the prognostic prediction of PI-treated myeloma patients was developed by the random survival forest variable hunting (RSF-VH) algorithm ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%